10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background: Intranasal drug delivery is a critical route for both systemic and targeted therapies, particularly for drugs intended to reach the central nervous system via the olfactory region. However, current aqueous nasal sprays have limited penetration beyond the anterior nasal airway, reducing their efficacy for nose-to-brain drug delivery. Nasal powder insufflators offer a promising alternative, as they allow higher drug payloads, typically up to 50 mg. The narrower spray cone angle of some powder insufflators has the potential for improved drug penetration, making them more suitable to deliver drugs higher and deeper into the nasal airways than is possible for aqueous nasal sprays. Despite this potential, existing methods for assessing powder deposition rely on complex and expensive imaging techniques such as gamma scintigraphy or MRI, limiting their accessibility for formulation and device optimization.Methods: This study presents a novel, cost-effective fluorescent imaging method to evaluate nasal powder deposition patterns using a transparent Koken nasal cast coated with synthetic mucus. Fluorescein-dyed spray-dried powders were delivered through a capsule-based nasal powder insufflator actuated by an air pulse, and deposition patterns were visualized under UV excitation. ImageJ analysis was used to quantify fluorescent intensity and distribution across five predefined nasal regions.Results: The results demonstrated that the powder delivery device successfully bypassed the anterior nasal airway and deposited a significant proportion of the dose in the olfactory region, achieving a mean posterior upper airway deposition of 51.7%, a substantial improvement over conventional aqueous sprays. The air pulse-actuated delivery mechanism also exhibited high repeatability, with a coefficient of variation of 14.9% in olfactory region deposition.Conclusion: By providing a simple, noninvasive alternative to radiolabeled imaging, this fluorescence-based approach enables rapid evaluation of nasal powder formulations and delivery devices. Hence, the approach described in this work could enable the nasal delivery device parameters, and powder formulation parameters to be optimized for nasal powder delivery devices. This could in turn allow drug delivery efficiency to different regions of the nose-particularly the upper nasal airways-to be optimized to suit different powder formulations, and different powder delivery devices.